1981
DOI: 10.1021/ac00230a043
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant atomic emissions of bromine and chlorine in the argon inductively coupled plasma

Abstract: Partial Grotrlan diagrams and tables of relative Intensities with corresponding wavelengths of 102 Inductively coupled plasma (ICP) excited, nonresonant atomic bromine emission lines and 85 ICP excited, nonresonant atomic chlorine emission lines are presented for the air-path, photomultiplier-accessible region 3700-9900 A and 4200-9900 A, respectively. Several (ICP) excited lines of Ionized Br and Cl are listed. Vertical emission Intensity profiles of near-infrared Br I and Cl I lines are presented for an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…By using this technique, Broekmen and Van Raaphorst studied the stable isotope dilution analysis of copper (6). Beary et al have reported a comparative study on isotope dilution copper analysis by using single-filament TIMS and inductively coupled plasma 0003-2700/88/0360-1812$01.50/0 mass spectrometry (ICP-MS) (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this technique, Broekmen and Van Raaphorst studied the stable isotope dilution analysis of copper (6). Beary et al have reported a comparative study on isotope dilution copper analysis by using single-filament TIMS and inductively coupled plasma 0003-2700/88/0360-1812$01.50/0 mass spectrometry (ICP-MS) (7).…”
Section: Methodsmentioning
confidence: 99%
“…Previous attempts in ICP optical emission spectroscopy (OES) to determine nonmetals have yielded only limited practical utility (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Although emission from many of these elements can be observed, it is typically detected only when relatively high concentrations of the analyte are present in the sample.…”
Section: Detection Of Negative Ions By Inductively Coupled Plasma Mas...mentioning
confidence: 99%
“…Absolute LODs for Br, Cl, S, and C were in the subnanogram range, as indicated in Table I. These values surpassed those reported for the near-IR lines by Fry and Hughes (12,13) by 2-3 orders of magnitude. This improvement was mainly attributed to the employment of the more sensitive vacuum UV lines, to the efficient optical sampling provided by the proximity of the plasma to the sampling orifice and entrance slit, and to the small dispersion of the sample plug provided by the low dead volume interface.…”
Section: Resultsmentioning
confidence: 58%
“…The C1165.7 nm line was chosen for carbon detection because it was more sensitive than the conventional C I line (193.1 nm) by a factor of 2-3. The relative LODs (ng mL"1 of Ar, Table II), which naturally depend on loop size, are also superior to those reported for the near IR lines (12,13) by several orders of magnitude.…”
Section: Resultsmentioning
confidence: 70%
“…Spectrometric elemental analysis of bulk metal alloys has had a rich history dating back to spark emission studies by Talbot in 1826 (1). Until the mid-1960s, arcs and sparks were the major sources for such analyses and are still in quite active use (2)(3)(4). While both techniques have been characterized extensively, their relatively high costs along with experimental and instrumental complexity can be prohibitive.…”
mentioning
confidence: 99%